Uji Iritasi Formulasi Sediaan Krim Ekstrak Bawang Dayak (Eleutherine bulbosa (Mill.) Urb) pada Kelinci Albino Putih - Syahrida Dian Ardhany; Rizky Ramadhani Effendie; Susi Novaryatiin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Based on research before, ethanolic extract of bawang dayak (Eleutherine bulbosa (Mill.) Urb) has been tested can inhibit the growth of acne-causing bacteria, therefore made an anti-acne cream for easy used. Thi study aims to know primary irritation activity of bawang dayak using patch test method. The results showed that the primary irritation index of control group (0.625< 2), P1 was 1g of cream (0.75< 2), P2 was 0.5g of cream (0<2) and P3 was 0.25g of cream (0< 2) in category of invisible irritation, so it can be concluded that the cream of ethanolic extract of bawang dayak topically does not irritate animals.